The Impact of Agricultural Sector on Food Security (Efficient: Indonesian Journal of Development Economics, 2023)
This study aims to determine the effect of workers in agricultural sector, income, access to clean water, and regional spending on food security in East Nusa Tenggara Province. This study uses panel data which is a combination of cross-section data from 22 districts/cities in East Nusa Tenggara Province and time series data from 2018-2021 which is then analyzed using multiple regression. The results show that the best estimation model is the Fixed Effect Model with the Generalized Least Squares (GLS) method. Based on the estimation result, it shows that the adjusted R2 is 0.91461. Assuming ceteris paribus, partially income and access to clean water has a significant positive effect on food security. Meanwhile, workers the agricultural sector has a significant negative effect on food security and local government expenditure has a non-significant positive effect on food security.